Development of somatic embryos for genetic transformation in Curcuma longa L. and Curcuma mangga Valeton & Zijp - Pikulthong, Vachiraporn; Teerakathiti, Tharathorn; Thamchaipenet, Arinthip; Peyachoknagul, Surin (Agriculture and Natural Resources, 2016)
Buds from rhizomes of Curcuma longa L. variety ‘Chumphon’ and Curcuma mangga Valeton & Zijp variety ‘Phetchaburi’ were cultured on Murashige and Skoog (MS) medium supplemented with 2.0 mg/L N6- benzyladenine (BA) for multiple shoot induction. Their shoots were cultured on MS medium supplemented with various concentrations of one of two plant growth regulators or a combination of bothd2,4-dichlorophenoxyacetic acid (2,4-D) and naphthaleneacetic acid (NAA). Interestingly, the medium containing both auxins (5 mg/L 2,4-D and 5 mg/L NAA) was best for somatic embryo induction after culturing for 4 weeks. Somatic embryo formation reached 87.50% for Curcuma longa and 95.83% for Curcuma mangga with a high quality of loose, friable and yellowish characters. The best conditions for the formation of shootlets occurred after transferring the somatic embryo toMS medium supplemented with 3.0 mg/L BA, 0.5 mg/L NAA and 3% maltose. The shootlets were rooted by transferring to MS medium containing 3.0 mg/L NAA. This is the first report of a complete in vitro regeneration system from somatic embryos of C. longa and C. mangga which was further used for gene manipulation in these plants. Diketide CoA synthase (DCS) and curcumin synthase (CURS) genes, which are the two genes involved in curcuminoid biosynthesis in turmeric, were cloned and transferred to these two species using Agrobacterium- mediated transformation. The presence of both target and marker genes, hpt, in the transformed somatic embryos was confirmed by polymerase chain reaction assay. After culturing, the transformed somatic embryos could survive for 4 weeks.